New Imaging Technologies to Enhance the Molecular Sensitivity of Positron Emission Tomography - Levin, Craig S. (Proceedings of the IEEE, 2008)
Positron emission tomography (PET) is used in the clinic and in vivo small animal research to study certain molecular processes associated with diseases such as cancer, heart disease, and neurological disorders and guide the discovery and development of new treatments. New PET molecular probes and associated small animal imaging assays are under development to target, visualize, and quantify subtle molecular and cellular processes such as protein-protein interactions in signal transduction pathways, cancer cell trafficking, therapeutic stem cells and their progeny, interaction of the immune system and tumor cells, and gene delivery and expression in living animals. These next-generation PET molecular imaging assays require an order of magnitude increase in PET's ability to detect, visualize, and quantify low concentrations of probe interacting with its target, which we will refer to as molecular sensitivity , in order to study the subtle signatures associated with these molecular processes. The molecular sensitivity is determined by a combination of the probe and biological/physiological properties of the subject that determine its specificity for the target, and the performance capabilities of the imaging system that determine how well the resulting signal can be measured. This paper focuses on the second aspect: the challenges of advancing PET technology and some of the new imaging system technologies under investigation to substantially enhance PET's molecular sensitivity. If successful, these novel imaging system technology advances, together with new probe molecules that target specific molecular processes associated with disease, will substantially enhance the molecular sensitivity of PET and thus increase its role in preclinical and clinical research as well as evaluating and managing disease in the clinic.